The production, allocation and cycling of carbon in a forest on fertile terra preta soil in eastern Amazonia compared with a forest on adjacent infertile soil - Doughty, Christopher E.; Metcalfe, Daniel B.; Costa, Mauricio C. da; Oliveira, Alex Antônio Ribeiro de; Neto, Guilherme F.C.; Silva, João A.; Aragao, L. E.O.C.; Almeida, Samuel Miranda; Quesada, Carlos Alberto; Girardin, Cécile A.J.; Halladay, Kate; Costa, Antônio Carlos Lôla da; et al. (Plant Ecology and Diversity, 2014)
Background: Terra preta do indio or 'dark earth' soils formed as a result of a long-term addition of organic matter by indigenous peoples in Amazonia. Aims: Here we report on the first study of productivity, allocation and carbon cycling from a terra preta plot in eastern Amazonia (Caxiuanã, Pará, Brazil), and contrast its dynamics with a nearby plot on infertile soil (ferralsols). Methods: We determined total net primary production (NPP) for fine roots, wood, and canopy and total autotrophic respiration (rhizosphere, wood, and canopy respiration) from two 1-ha plots on contrasting soils. Results: Both gross primary productivity (GPP) (35.68 ± 3.65 vs. 32.08 ± 3.46 Mg C ha-1 year-1) and carbon use efficiency (CUE) (0.44 ± 0.06 vs. 0.42 ± 0.05) were slightly higher at the terra preta plot. Total NPP (15.77 ± 1.13 Mg C ha-1 year-1 vs. 13.57 ± 0.60 Mg C ha-1 year-1) and rates of fine root production (6.41 ± 1.08 vs. 3.68 ± 0.52 Mg C ha-1 year-1) were also greater at the terra preta plot vs. the tower plot. Conclusions: Forests on terra preta soil fix slightly more carbon and allocate slightly more of that carbon towards growth than forests on the infertile plot, which leads to greater total NPP, which was disproportionately allocated to fine roots. However, since increased fine root NPP was partially offset by increased heterotrophic soil respiration, the increased root growth was unlikely to greatly enhance soil carbon stocks in terra preta soils. © 2014 Copyright 2013 Botanical Society of Scotland and Taylor & Francis.